The prevalence, predictors and outcomes of guideline‐directed medical therapy in patients with acute myocardial infarction undergoing PCI, an analysis from the PROMETHEUS registry. Issue 3 (23rd October 2018) - Ge, Zhen; Baber, Usman; Claessen, Bimmer E.; Farhan, Serdar; Chandrasekhar, Jaya; Li, Shawn X.; Sartori, Samantha; Kini, Annapoorna S.; Rao, Sunil V.; Weiss, Sandra; Henry, Timothy D.; Vogel, Birgit; et al.
Abstract: Objectives: To investigate the prevalence, predictors and associations between guideline‐directed medical therapy (GDMT) and clinical outcomes in acute myocardial infarction (AMI) patients undergoing percutaneous coronary intervention (PCI) from eight academic centers in the United States. Background: Evidence for GDMT in patients with AMI comes from randomized controlled trials. The use of GDMT in clinical practice is unknown in this setting. Methods: PROMETHEUS is a multicenter observational registry comprising 19, 914 patients with acute coronary syndrome (ACS) undergoing PCI. Patients with AMI were divided into two groups based on the prescription of GDMT or not (non‐GDMT) at discharge. GDMT was defined according to American College of Cardiology/American Heart Association (ACC/AHA) class I recommendations, specifically, dual antiplatelet therapy, statin and beta‐blocker for all AMI patients, and additional ACEI/ARB in patients with left ventricular ejection fraction (LVEF) less than 40%, hypertension, diabetes mellitus (DM) or chronic kidney disease (CKD). The primary endpoint was major adverse cardiovascular events (MACE) defined as a composite of all‐cause death, MI, stroke or unplanned target vessel revascularization (TVR) at 1 year. Results: Out of 4, 834 patients with AMI, 3, 356 (69.4%) patients were discharged on GDMT. Patients receiving GDMT were more often younger and male. Compared with non‐GDMT patients, GDMT patients had a significantly lower frequency of comorbidities. Predictors of greater GDMT prescription at discharge were ST‐segment elevation myocardial infarction (STEMI), and increased body mass index (BMI), whereas hypertension, prior PCI, anemia and CKD were associated with less GDMT prescription. At 1 year, the use of GDMT was associated with a significantly lower incidence of MACE (13.7% vs. 22.5%; adjusted HR 0.68; 95%CI 0.58–0.80; P < 0.001), death (3.7% vs. 9.4%; adjusted HR 0.61; 95%CI 0.46–0.80; P < 0.001), and unplanned TVR (8.4% vs. 11.3%; adjusted HR 0.76; 95%CI 0.61–0.96; P = 0.020). However, there were no significant differences in the incidence of MI (4.3% vs. 7.0%; adjusted HR 0.75; 95%CI 0.56–1.01; P = 0.056), stroke (1.5% vs. 2.0%; adjusted HR 0.79; 95%CI 0.47–1.34; P = 0.384) between the two groups. Conclusion: In a contemporary practice setting in the United States, GDMT was utilized in just over two‐thirds of AMI patients undergoing PCI. Predictors of GDMT prescription at discharge included STEMI, BMI and absence of hypertension, CKD, anemia or prior PCI. Use of GDMT was associated with significantly lower risk of 1‐year MACE and mortality.